Poultry genetics, breeding, and biotechnology - Aggrey, S. E.; Muir, W. M. [ (William M.)] (CABI Publishing, 2003)
This reference work addresses issues associated with poultry breeding, by examining quantitative and molecular genetics and the uses of transgenic technology. The important area of genetic disease resistance and transmission is also covered.